Seed system innovation to accelerate access to robust potato varieties - International Potato Center (International Potato Center, 2022)
This video describes the International Potato Center’s work in Uganda to build more effective seed systems for delivering more robust potato varieties to smallholder farmers. Special thanks to our many Ugandan partners featured in this video.